1997
DOI: 10.1094/phyto.1997.87.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Leptosphaeria maculans in Brassica juncea

Abstract: The inheritance of resistance to Leptosphaeria maculans, the causal agent of black leg of crucifers, was studied in Brassica juncea. Three resistant accessions (UM3021, UM3043, and UM3323) and one susceptible accession (UM3132) of B. juncea were crossed in a complete diallel. Parents, F(1), and F(2) progenies were evaluated for all crosses using both cotyledon and stem inoculation. Cotyledon reaction was evaluated with two isolates of L. maculans, but stem reaction was evaluated with one isolate. Disease react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Through RFLP analysis Dixelius and Wahlberg (1999) identified three conserved regions in the B genome that contain genes for both seedling and adult leaf resistance. In B. juncea, resistance to L. maculans (in the seedling and adult plant) appears to be controlled by two genes with dominantrecessive epistatic interaction (Keri et al 1997) which could be identical to genes found in the B genome introgressions. From the results compiled by these researchers, one might conclude that oligogenic control of resistance exists in both the seedling and adult (stem, leaf) tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Through RFLP analysis Dixelius and Wahlberg (1999) identified three conserved regions in the B genome that contain genes for both seedling and adult leaf resistance. In B. juncea, resistance to L. maculans (in the seedling and adult plant) appears to be controlled by two genes with dominantrecessive epistatic interaction (Keri et al 1997) which could be identical to genes found in the B genome introgressions. From the results compiled by these researchers, one might conclude that oligogenic control of resistance exists in both the seedling and adult (stem, leaf) tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Based on cotyledon and stem resistance ratings, Keri et al (1997) suggested that resistance in B. juncea is mediated by two genes. This is consistent with genetic data obtained with L. maculans, which showed that the interaction was governed by two avirulence genes termed AvrLm5 and AvrLm6 (Balesdent et al, 2002).…”
Section: Genes Identified In Other Brassica Speciesmentioning
confidence: 99%
“…Screening of cultivated accessions of Brassica oleracea L. and B. rapa (A genome) has not identified many accessions with resistance to L. maculans. Keri et al (1997) studied resistance in three accessions of B. juncea crossed with a susceptible accession (UM3132) to two isolates (PG2) of L. maculans and demonstrated that resistance was controlled by one dominant and one recessive gene. A similar two gene dominant-recessive interaction was found using a cross with a resistant cultivar, 'AC Vulcan', and the same susceptible line, UM3132.…”
Section: Types and Sources Of Resistancementioning
confidence: 99%